2008
DOI: 10.1159/000151672
|View full text |Cite
|
Sign up to set email alerts
|

Etiology, Prenatal Diagnostics and Outcome of Ventriculomegaly in 230 Cases

Abstract: Objective: The aim of this study was to review and summarize the information regarding the etiology, diagnostics and outcome of ventriculomegaly. Methods: The study included 230 cases of ventriculomegaly examined between 1979 and 2000. The main diagnostic criterion for ventriculomegaly was the transverse diameter of the ventricular atrium at the level of the glomus of the chorioid plexus measuring >10 mm, irrespective of gestational age. Results: Gender distribution (male:female ratio: 0.98) coincided with tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 49 publications
2
2
0
Order By: Relevance
“…In our series, 53% of the fetal VM cases were diagnosed ≤ 24 weeks' and 7.4% after 32 weeks' gestation. Joo´ et al reported that 60% of the prenatal diagnosis in their series was made before the 24th gestational weeks' [14]. Incidences of mild, moderate and severe VM cases in our study group are also in accordance with other studies [5,15].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our series, 53% of the fetal VM cases were diagnosed ≤ 24 weeks' and 7.4% after 32 weeks' gestation. Joo´ et al reported that 60% of the prenatal diagnosis in their series was made before the 24th gestational weeks' [14]. Incidences of mild, moderate and severe VM cases in our study group are also in accordance with other studies [5,15].…”
Section: Discussionsupporting
confidence: 92%
“…The mean maternal age and the average gestational age at the rst diagnoses of fetal VM cases in our study population are similar to those reported in the literature [5,8,14]. In our series, 53% of the fetal VM cases were diagnosed ≤ 24 weeks' and 7.4% after 32 weeks' gestation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Treatment strategies for obstructive hydrocephalus have been thoroughly explored, and numerous studies have investigated exclusive treatment strategies and their effectiveness. ETV is a preferred technique for obstructive hydrocephalus rather than traditional shunting procedures in selected patients at neurosurgical centers in developing countries with neuroendoscopy facility and expertise 17 . This growing popularity is because of the fact that ETV affords the patient with shunt-free functionality and is successful remedy for hydrocephalus no matter etiology, patient age, and other elements 18 .…”
Section: Discussionmentioning
confidence: 99%